Enhancing the Nutritional Quality of Major Food Crops Through Conventional and Genomics-Assisted Breeding - Gaikwad, Kiran B.; Rani, Sushma; Kumar, Manjeet; Gupta, Vikas; Babu, Prashanth H.; Bainsla, Naresh Kumar; Yadav, Rajbir (Frontiers in Nutrition, 2020)
Nutritional stress is making over two billion world population malnourished. Either our commercially cultivated varieties of cereals, pulses, and oilseed crops are deficient in essential nutrients or the soil in which these crops grow are becoming devoid of minerals. Unfortunately, our major food crops are poor sources of micronutrients required for normal human growth. To overcome the problem of nutritional deficiency, greater emphasis should be laid on the identification of genes / QTLs pertaining to essential nutrients and their successful deployment in the elite breeding lines through marker-assisted breeding. The manuscript deals in the information on identified QTLs for protein content, vitamins, macronutrients, micro-nutrients, minerals, oil content, and essential amino acids in the major food crops. These QTLs can be utilized in the development of nutri-rich crop varieties. Genome editing technologies that can rapidly modify genomes in a precise way andwill directly enrich the nutritional status of an elite varieties could hold a bright future to address the challenge of malnutrition.